The Effect of Information Overload on Decision Difficulty Mediated by Consumer Confusion in Generation Z in Jepara - Putri, Rima Zuliana; Roosdhani , Mohamad Rifqy (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
This study aims to analyze how Information Overload impacts decision difficulty mediated by Consumer Confusion on generation Z in Jepara. The target of this study is generation Z in Jepara. This study uses quantitative methods. The source of research data uses Primary Data. The survey was conducted through Google Form, the sampling method in this study was random sampling, and 310 respondents were taken as samples. This study uses Smart (PLS), with the SmartPLS Version 4.0 application to conduct statistical analysis. The results show that there are findings that Information overload has a positive relationship with decision difficulty, and between consumer confusion and decision difficulty, the results of consumer confusion mediation are positively correlated.